INSTAGRAM CONTENT DESIGN STRATEGY TO BOOST CONSUMER APPEAL FOR EL BEAUTY SALON ON SOCIAL MEDIA EL BEAUTY - Ummu Sarofah; Agusti; Siti Seituni (Yayasan Amanah Nur Aman, 2025)
Instagram social media, which was originally shown as a photo and video sharing application between users, is now increasingly shifting because it is used to promote a product/service. These results are based on the increasing use of Instagram which is getting faster every day, so that it is used as an opportunity by business actors who are already big or just starting a business. Instagram content design responds to this phenomenon which is proven by the increase in features to support marketing. Many things can be used by services/products to develop their companies with Instagram content design to promote products and services. However, not many business actors use Instagram features other than in the form of photos and content. This study uses a literature review method and is studied with the theory of visual elements, content, and theories related to marketing a content. The results of the study using the literature review method show that the Instagram content design strategy on social media is very efficient in increasing consumer appeal on social media for the El Beauty salon.